Pemanfaatan Akun Instagram @dispusipdajabar Dalam Pemenuhan Kebutuhan Informasi Followers - Kaffah, Silmi; Indah, Rosiana Nurwa; Syam, Rifqy Zaeni Achmad (Media Nusantara, 2021)
This study aims to determine the utilization of the @dipusipdajabar Instagram account in fulfilling followers’ information needs. The specific objective of this study is to find out (1) the material submitted by the @dipuspdajabar Instagram account in providing information (2) The speed of the Instagram account @dipusipdajabar in providing information. (3) The accuracy of the @dipusipdajabar Instagram account in providing content information (4) User response to the @dipusipdajabar Instagram account. The method used in this research is the descriptive method with a qualitative approach. As for data collection obtained through observation, interviews, and documentation. From the results of the study, it can be concluded that the use of the @dipusipdajabar Instagram account in fulfilling the information needs of followers has been very effective, seen from the material presented in accordance with the purpose of the information provided by the @dipusipdajabar Instagram account, The speed given is also very fast, right in providing information and user responses that have been very good in every information provided by the @dipusipdajabar Instagram account.